Podcasts are fashionable too: the use of podcasting in fashion communication - Fernandes, Clara (2021)
This exploratory article seeks to analyse how fashion, as a theme with a strong aesthetic and artistic component, has been worked on by podcasting. We start from the idea that today social media represent an essential field for the communication of brands in the fashion industry, mainly due to its visual component and because it is in these spaces that influencers, key players in current dissemination strategies, are found. Considering these new forms of communication and knowing the growth that podcasts have registered, we explore the potential that this medium can have in connecting with consumers. Based on a selection of fifteen fashion podcasts, we analyse the extent to which podcasting has been a territory for promoting the fashion industry.